IMPLEMENTASI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) UNTUK PENINGKATAN MOTIVASI BELAJAR SISWA KELAS 5 SDN PALEBON 02 SEMARANG - Sa`adah, Miayatus; Sulianto, Joko; Nindyasari, Wrestika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The low motivation of students to learn Pancasila Education is generally caused by the limited variety of teaching methods and media used during the learning process, resulting in a conventional and teacher-centered approach. This research aims to use Culturally Responsive Teaching (CRT) to improve the learning motivation of fifth-grade students at SDN Palebon 02. A Classroom Action Research (CAR) approach was employed through two cycles in this study. The research subjects consisted of twenty-eight fifth-grade students at SDN Palebon 02. Data were collected through observations and questionnaires, and qualitative descriptive analysis was used. Based on the research results, using the CRT approach increased students' learning enthusiasm by 7%, from 52% in the low category before the pre-cycle to 59% in the sufficient category in the first cycle. In the very high category, there was a 26% increase from the first cycle to the second cycle, reaching 85%. Applying the CRT approach effectively increased the learning motivation of elementary school students in Pancasila Education.